The role of nutrition in the prevention of iron deficiency anemia - Manikam, Nurul Ratna (World Nutrition Journal, 2025)
The prevalence of iron deficiency anemia (IDA) among children under five is approximately 25%. IDA is characterized with low hemoglobin levels and depleted iron stores, commonly due to inadequate intake, increase requirement, malabsorption, or chronic blood loss. IDA has significant implications for growth, cognitive development, and immunity